2021
DOI: 10.3390/su13137442
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Walkable Streets during the COVID-19 Pandemic in a Suburban City in the Osaka Metropolitan Area

Abstract: The purpose of this study was to identify the walkable streets where traffic behavior changed according to each residential cluster during the COVID-19 pandemic. By elucidating the changes, it is possible to identify streets that should be redesigned following the changes in traffic behavior in relation to human mobility. This study analyzed Ibaraki City, a suburban city located in the Osaka Metropolitan Area. The analysis compared the panel data of the GPS Location History for April 2020 and April 2019. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
3
17
0
1
Order By: Relevance
“…The analysis was conducted on panel data from April 2019 to April 2020 using the case study of Ibaraki City. The period and area of the LH data are the same as that of the studies of Kato [14] and Kato et al [15]. Using the LH data, this study clarified the home range by utilizing MCP.…”
Section: Purposementioning
confidence: 86%
See 3 more Smart Citations
“…The analysis was conducted on panel data from April 2019 to April 2020 using the case study of Ibaraki City. The period and area of the LH data are the same as that of the studies of Kato [14] and Kato et al [15]. Using the LH data, this study clarified the home range by utilizing MCP.…”
Section: Purposementioning
confidence: 86%
“…During the first state of emergency in Ibaraki City in Osaka Metropolitan area, Kato [14] reported that dense human space-times were formed in the parks as well as in the stations. Similarly, Kato et al [15] reported an increasing number of bicycle trips. Those studies suggest that the home range might be decreased to the neighborhood scale due to the state of emergency.…”
Section: Introduction 1backgroundmentioning
confidence: 85%
See 2 more Smart Citations
“…Since 2019, walkability has begun to attract attention because urban policies related to walkability are being developed. Kato [7] and Kato et al [8,9] clarified that the COVID-19 (Coronavirus Disease 2019) pandemic accelerated the need for walkable neighborhoods in the Osaka metropolitan area. Therefore, it is essential to understand the impact of walkability on future populations, as this will enable us to take a practical approach to future urban planning.…”
Section: Introduction 1backgroundmentioning
confidence: 99%